Global and regional governance of One Health and implications for global health security. Issue 10377 (25th February 2023) - Elnaiem, Azza; Mohamed-Ahmed, Olaa; Zumla, Alimuddin; Mecaskey, Jeffrey; Charron, Nora; Abakar, Mahamat Fayiz; Raji, Tajudeen; Bahalim, Ammad; Manikam, Logan; Risk, Omar; Okereke, Ebere; Squires, Neil; et al.
Summary: The apparent failure of global health security to prevent or prepare for the COVID-19 pandemic has highlighted the need for closer cooperation between human, animal (domestic and wildlife), and environmental health sectors. However, the many institutions, processes, regulatory frameworks, and legal instruments with direct and indirect roles in the global governance of One Health have led to a fragmented, global, multilateral health security architecture. We explore four challenges: first, the sectoral, professional, and institutional silos and tensions existing between human, animal, and environmental health; second, the challenge that the international legal system, state sovereignty, and existing legal instruments pose for the governance of One Health; third, the power dynamics and asymmetry in power between countries represented in multilateral institutions and their impact on priority setting; and finally, the current financing mechanisms that predominantly focus on response to crises, and the chronic underinvestment for epidemic and emergency prevention, mitigation, and preparedness activities. We illustrate the global and regional dimensions to these four challenges and how they relate to national needs and priorities through three case studies on compulsory licensing, the governance of water resources in the Lake Chad Basin, and the desert locust infestation in east Africa. Finally, we propose 12 recommendations for the global community to address these challenges. Despite its broad and holistic agenda, One Health continues to be dominated by human and domestic animal health experts. Substantial efforts should be made to address the social–ecological drivers of health emergencies including outbreaks of emerging, re-emerging, and endemic infectious diseases. These drivers include climate change, biodiversity loss, and land-use change, and therefore require effective and enforceable legislation, investment, capacity building, and integration of other sectors and professionals beyond health.